2021
DOI: 10.3390/s22010185
|View full text |Cite
|
Sign up to set email alerts
|

An Aggregated Mutual Information Based Feature Selection with Machine Learning Methods for Enhancing IoT Botnet Attack Detection

Abstract: Due to the wide availability and usage of connected devices in Internet of Things (IoT) networks, the number of attacks on these networks is continually increasing. A particularly serious and dangerous type of attack in the IoT environment is the botnet attack, where the attackers can control the IoT systems to generate enormous networks of “bot” devices for generating malicious activities. To detect this type of attack, several Intrusion Detection Systems (IDSs) have been proposed for IoT networks based on ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The suggested approach demonstrated efficient sequential analysis in improving IoT security. The research [19] suggested a novel method for improving botnet attack detection in IoT networks. They used an aggregated mutual information-based feature selection method combined with ML techniques.…”
Section: Related Workmentioning
confidence: 99%
“…The suggested approach demonstrated efficient sequential analysis in improving IoT security. The research [19] suggested a novel method for improving botnet attack detection in IoT networks. They used an aggregated mutual information-based feature selection method combined with ML techniques.…”
Section: Related Workmentioning
confidence: 99%
“…While augmentation-based solutions, such as oversampling or synthetic data generation, can help to increase the amount of available data and improve the performance of information theory-based feature selection methods, there are also potential drawbacks to consider. One potential issue with augmentation-based solutions is the risk of introducing bias or noise into the data [ 44 ]. Oversampling, for example, can lead to the overrepresentation of certain classes or instances in the data, which can bias the machine learning algorithm towards these classes or instances.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies have shown that feature selection is crucial for improving the performance of intrusion detection systems (IDS) in various IoT environments [ 42 , 43 , 44 ]. One of the most commonly used feature selection techniques is the filter approach, which selects features based on their statistical properties and relevance to the problem [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations